The competitive dynamics of two Protea shrubs growing in a mixed fynbos stand - Anderson, Pippin (Department of Biological Sciences, 2017)
Patterns of segregation among Protea species were investigated. Interspecific competition was studied as a cause of these patterns. Two different methods were used for measuring competition in a mixed stand of P. lepidocarpodendron and P. corona/a growing on the Cape Peninsula. These were the plot-based averaging method, which considers stand density, and the nearest neighbour approach, which considers competitive impacts as a function of the immediate neighbouring plant. Both methods demonstrated negligible interspecific, and strong intraspecific competitive effects on fecundity. However strong interspecific competition appears to be occurring at earlier stages of the life cycle and may account for habitat segregation of P. coronata and P. lepidocarpodendron. P. lepidocarpodendron juveniles appear to outgrow and suppress P. coronata plants. Survivors of this interaction grow to full maturity, giving an apparent lack of species interactions when measured in terms of fecundity. The same results were demonstrated in a mixed stand of P. lepidocarpodendron and H. suaveolens, where H. suaveolens suppresses P. lepidocarpodendron. The study indicates the importance of shrub architecture in reducing species interactions, and juvenile phase properties in determining competitive displacement. Soil preferences and variable fire responses between the species were studied in an attempt to explain the restricted distribution of the stronger competitor, P. lepidocarpodendron at the study site. No conclusions were reached, but the restriction of this species from certain sites appears to be a fire response.